Wind Turbine vibration based SHM system: influence of the sensors layout and noise. (2017) - Pacheco, João; Oliveira, Gustavo; Magalhães, Filipe; Cunha, Álvaro; Caetano, Elsa
Abstract: With the goal of reducing the investment in monitoring equipment and simultaneously keep an adequate accuracy in structural condition assessment, this paper studies the results that can be obtained with different strategies of instrumentation of a 2.0 MW onshore wind turbine. The data processing strategy is based on the continuous tracking of the wind turbine main vibration modes using Operational Modal Analysis techniques combined with algorithms that deal with the particularities of operation of the wind turbines and that permit an online automated identification. A database of continuously collected acceleration time series during one year is used to evaluate the efficiency on the monitoring system on the detection of simulated damage scenarios, considering variations on the number of sensors, on their distribution in the wind turbine tower and on their noise level.